THE PHILOSOPHICAL PERSPECTIVE OF FEMINISM IN THE FIGHT FOR WOMEN'S RIGHTS - Audi Pratama; Kurniati Kurniati (ANAYASA : Journal of Legal Studies, 2026)
This study discusses feminist perspectives on morality and rationality in fighting for women's rights by highlighting how traditional moral and rational structures are often built on a patriarchal perspective that ignores women's experiences and judgments. Philosophical feminism views that morality and rationality, which have been understood in a patriarchal manner, have placed women in a position of subordination and limited their mobility in both the public and private spheres. This study uses a literature review method by collecting various sources such as books, scientific journals, and articles discussing feminist philosophy and the concept of freedom. The results of the study show that feminism emphasizes the importance of legal and public policy reform to achieve gender equality, as well as fighting for women's freedom in determining their personal and professional life choices. In addition, third-wave feminism, influenced by postmodernism, affirms the diversity of women's identities and experiences, rejecting a single generalization about women. In the context of law, feminism plays a role in criticizing systems that reinforce patriarchy and limit women's access to justice. Thus, the feminist perspective makes an important contribution to reinterpreting morality and rationality towards a more gender-equitable social order.